Maintaining mental health and function for the long run in cystic fibrosis. (October 2016) - Smith, Beth A.; Georgiopoulos, Anna M.; Quittner, Alexandra L.
Summary: Research shows that individuals with cystic fibrosis (CF) and their families experience significant emotional morbidity. In addition to distress, worry, and grief, high rates of clinically significant symptoms of depression and anxiety have been found in both individuals with CF and parents. These disorders have a major impact on the person's functioning, and that of their family, and adversely impact the capacity to cope with the burden of CF and adhere to prescribed treatments. Despite growing recognition that mental health care is an essential component of comprehensive CF care, evidence suggests many patients and their families do not receive needed support and mental health interventions. Clinical practice guidelines for screening and treating depression and anxiety in individuals with CF have been developed by The Cystic Fibrosis Foundation and the European Cystic Fibrosis Society in response to this need. This review highlights that the optimum care for individuals with CF and their families incorporates mental health in routine CF care. Addressing mental health could substantially improve physical and mental health outcomes and the functioning of individuals with CF and their families.Pediatr Pulmonol. 2016;51:S71–S78. © 2016 Wiley Periodicals, Inc.